A Comprehensive Review of High-Impact Educational Research (2021–2025): Trends, Insights, and Emerging Practices - Dr. Muhammad Rafiq-uz-Zaman; Yi-Huang Shih (Inverge Journal of Social Sciences, 2026)
The literature review is a critical analysis of high-impact educational research published between 2021 and 2025, which identifies the most significant trends, evidence-based practices, and emerging innovations that influence the development of modern education. Pedagogical practices in the post-COVID period have changed to emphasize the effectiveness of student engagement, fair access, and the implementation of technology-based approaches to instruction. Personalized and adaptive learning with the help of digital transformation (artificial intelligence, interactive e-books, and immersive learning environments) has resulted in a measurable student performance and engagement improvement. Problem-Based Learning, Project-Based Learning, and formative assessment remain active learning approaches that support the development of critical thinking and problem-solving skills in a variety of educational settings. These advances notwithstanding, there are still issues such as gaps in teacher training, a lack of resources, and professional development. The new technologies hold the promise of innovation but pose threats to data privacy, algorithmic bias, and digital equity. These challenges cannot be met without systemic support, accountable AI implementation, and a commitment on the part of institutions to inclusive and student-centred learning. This review will summarize the existing literature and outline practical recommendations to be followed by policymakers, teachers, and scholars who want to maximize the learning process and overcome the changing digital environment. References Ajid, S. N., Kusumaningtyas, D., Ratih, K., & Lava, S. (2025). Strategies for Integrating Problem-Based Learning, Teaching Modules, and Formative Assessments to Enhance Learning Outcomes and Critical Thinking Skills. Indonesian Journal on Learning and Advanced Education (IJOLAE), 7(2), 340–357. https://doi.org/10.23917/ijolae.v7i2.8612 Albohamood, A. H., Alqattan, M. S., & Vizcarra, C. P. (2025). Real-time Student Engagement Monitoring in Classroom Environments using Machine Learning and Computer Vision. 2025 4th International Conference on Computing and Information Technology (ICCIT), 1–6. https://doi.org/10.1109/ICCIT63348.2025.10989406 Andayani, A., & Prabowo, S. (2025). HOTS-Based Interactive E-Books and Student Learning Outcomes: A Systematic Literature Review. International Journal of Education and Learning Studies, 1(3), 45–58. https://doi.org/10.64421/ijels.v1i3.23 Bashir, M., & Naseer, D. N. (2025). From Opportunity to Obstacle: Learners’ Experiences on the Use of Campus Management System. Inverge Journal of Social Sciences, 4(1), 148–161. https://doi.org/10.63544/ijss.v4i1.196 Bayani, F., Rokhmat, J., Hakim, A., & Sukarso, A. (2025). Research Trends in Analytical Thinking Skills for Science Education: Insights, Pedagogical Approaches, and Future Directions. International Journal of Ethnoscience and Technology in Education, 2(1), 52–68. https://doi.org/10.33394/ijete.v2i1.14142 Bensi, L. P., Bensi, M. E., Oliveros, A. G. G., & Torres, R. A. G. (2025). Student Preferences for Hybrid Versus Face-to-Face Learning Approaches: A Comparative Analysis of Engagement, Learning Outcomes, and Technological Challenges. International Journal of Research and Scientific Innovation, 12(3), 881–892. https://doi.org/10.51244/ijrsi.2025.12030074 Bizimana, E. (2025). Student Engagement in Learning: Exploring the Role of Perceived Student Cohesiveness, Equity, Teacher Support, and Teacher Autonomy Support Under the Framework of Self-Determination Theory. International Journal of Changes in Education. Advance online publication. https://doi.org/10.47852/bonviewijce52024500 Cena, J. F., Diez, M. B., Flores, M. R., Noquiao, H. P. P., & Quinco-Cadosales, M. N. (2025). Interactive Self-Learning Modules (ISLMs) in Sustaining Student Engagement and Learning Outcomes: A Meta-Synthesis. International Journal of Advanced Multidisciplinary Research and Studies, 5(4), 153-160. https://doi.org/10.62225/2583049x.2025.5.4.4782 Chow, W., Xu, B., Bhaumik, A., Peng, S., Guo, M., & Kurnia, S. (2025). Bridging Engagement and Learning Outcomes. Pacific Journal of Technology Enhanced Learning, 7(2), 29–30. https://doi.org/10.24135/pjtel.v7i2.224 Copland, S., Hills, M., & McKendrick-Calder, L. (2025). Structured Flexibility in Assessment: Students Perceptions of the Impact of Different Elements of Choice on Their Decision Making, Engagement, and Learning Experiences. Teaching and Learning Inquiry, 13, 1–18. https://doi.org/10.20343/teachlearninqu.13.61 Edmunds, T. K., & Little, R. (2025). Impacts of the Active Learning Classroom on Student Learning and Engagement: The Role of Technology. Canadian Journal for the Scholarship of Teaching and Learning, 16(1), Article 9. https://doi.org/10.5206/cjsotlrcacea.2025.1.16584 Firdaus, T., Mufidah, R., Hamida, R. N., Febrianti, R. I., & Guivara, A. E. R. (2025). Research trends and the impact of ChatGPT on educational environments. International Journal of Social Sciences and Education Research, 11(2), 112–128. https://doi.org/10.24289/ijsser.1609741 Fitratunisyah, F., Bactiar, I., & Jamaluddin, J. (2025). Research Trends of Problem Based Learning (PBL) Models to Improve Students' Critical Thinking Skills and Learning Outcomes (2016-2025): A Systematic Review. Current Educational Review, 1(4), 331–348. https://doi.org/10.56566/cer.v1i4.410 Hamdan, A., Elmunsyah, H., Maula, P. I., Sari, H. V., Abdullah, M. F., & Septianingsih, D. (2025). Systematic Evaluation of Adaptive Assessment in E-Learning: Contribution to Vocational Education. 2025 9th International Conference on Electrical, Electronics and Information Engineering (ICEEIE), 1–6. https://doi.org/10.1109/ICEEIE66203.2025.11254863 Huang, X., Gai, Y., Sun, L., Zhang, Y., Yang, D., Sheng, H., Huang, J.-M., & Li, Y. (2025). Research on Strategies for Enhancing Student Engagement and Retention in Engineering Education under a Technology-Enhanced Learning Environment. 2025 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE), 1–6. https://doi.org/10.1109/TALE66047.2025.11346628 Irvani, A. I., Dewi, A. P., Gunawan, A., & Rahmaniar, A. (2025). Gamification and Student Engagement: Evidence, Challenges, and Future Directions. Eduscape: Journal of Education Insight, 3(3), 175–189. https://doi.org/10.61978/eduscape.v3i3.937 Jainuri, M., Kamid, K., Syaiful, S., & Huda, N. (2025). Microlearning Effectiveness in Higher Education: A Systematic Review and Meta-Analysis of Student Retention and Learning Outcomes. MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 7(2), 476–492. https://doi.org/10.33365/jm.v7i2.517 K, N., Kumar, B. H., Sonar, R., Lamba, A. K., Valiveti, V. S. M., & Kalra, G. (2025). Enhancing Student Engagement and Learning Outcomes in Higher Education through E-Learning and Restricted Boltzmann Machines. 2025 3rd International Conference on Data Science and Information System (ICDSIS), 1–5. https://doi.org/10.1109/ICDSIS65355.2025.11071086 Khan, M. (2025). Mentimeter Tool for Enhancing Student Engagement and Active Learning: A Literature Review. International Journal of Changes in Education. Advance online publication. https://doi.org/10.47852/bonviewijce52023801 Kristiyuana, K., Wuriningsih, Fr., Idammatussilmi, I., & Agung, A. (2025). Reforming Pedagogy in Indonesian Primary Schools: A Five-Year Systematic Review of Differentiated Instruction, Project-Based Learning, and Formative Assessment (2020-2025). Jurnal Ilmiah Profesi Pendidikan, 10(2), 1556–1569. https://doi.org/10.29303/jipp.v10i2.3413 Laid, S. M. T., & Adlaon, M. S. (2025). A Systematic Review of Innovative Teaching Strategies in Science: Exploring Hands-on Learning, Technology Integration, and Student-Centered Approaches. Acta Pedagogia Asiana, 4(2), 91–105. https://doi.org/10.53623/apga.v4i2.645 Le, U. M., Kassem, T., & Tran, T. (2025). Enhancing pharmaceutical calculation proficiency: Exploring self-directed learning and self-reinforcement assessment strategies for student success. Currents in Pharmacy Teaching and Learning, 17(6), Article 102323. https://doi.org/10.1016/j.cptl.2025.102323 Li, F., Liu, J., Wu, J., & Wu, Z. (2025). Personalized Learning in Graduate Education: Learning Analytics and Assessment Methods from an IT Industry Perspective. 2025 7th International Conference on Computer Science and Technologies in Education (CSTE), 201–206. https://doi.org/10.1109/CSTE64638.2025.11091918 Martín-Rodríguez, A., & Madrigal-Cerezo, R. (2025). Technology-Enhanced Pedagogy in Physical Education: Bridging Engagement, Learning, and Lifelong Activity. Education Sciences, 15(4), Article 409. https://doi.org/10.3390/educsci15040409 Maurer, M., & Aleem, S. (2025). Comparative Performance Analysis of Machine Learning Techniques for Engagement Assessment in Education. 2025 International Conference on Artificial Intelligence, Computer, Data Sciences and Applications (ACDSA), 128–133. https://doi.org/10.1109/ACDSA65407.2025.11166367 Nassiri, S. H., & Bunyamin, M. A. H. (2025). TRENDS AND RESEARCH FRONTIERS IN PHYSICS EDUCATION: A BIBLIOMETRIC ANALYSIS FROM YEAR 2021-2025. International Journal of Modern Education, 7(27), 626–642. https://doi.org/10.35631/ijmoe.727039 Ningsih, A. G. (2025). Exploring the Impact of Adaptive Real-Time Quiz Platforms with Differentiated Learning Features on Student Engagement and Learning Outcomes: A Mixed-Methods Approach. International Journal of Information and Education Technology, 15(6), 1165–1175. https://doi.org/10.18178/ijiet.2025.15.6.2329 Ojetunde, S., & Ramnarain, U. (2025). Like objects or like subjects? Effects of student-robot interaction (SRI) and mathematical ability on students learning outcomes. Smart Learning Environments, 12(1), Article 11. https://doi.org/10.1186/s40561-024-00345-2 Punnoose, N. J., Mathew, M. d., & Baxi, V. (2025). Enhancing Student Engagement Through a Curated Digital Learning Library Platform. 2025 World Engineering Education Forum - Global Engineering Deans Council (WEEF-GEDC), 1–5. https://doi.org/10.1109/WEEF-GEDC66748.2025.11256211 Razilu, Z., Sulfasyah, S., & Nappu, S. (2025). Mapping Global Research Trends in Interactive Learning Media: A Bibliometric Analysis of Scopus Publications (2021-2025). PPSDP International Journal of Education, 4(2), 411–424. https://doi.org/10.59175/pijed.v4i2.743 Ricky, A. S., Umamah, F., Amalia, S. N., & Trisnawati, E. (2025). SYSTEMATIC LITERATUR REVIEW (2021-2025): PENGEMBANGAN E-BOOK INTERAKTIF DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR. EDUTECH: Jurnal Inovasi Pendidikan Berbantuan Teknologi, 5(3), 464–474. https://doi.org/10.51878/edutech.v5i3.6887 Rohman, A. Z., Hasaini, H. F., Setiawan, R., & Rumagit, R. Y. (2025). Predictive Framework for Adaptive Learning: Integrating Clickstream Analytics and Assessment Outcomes in LMS. 2025 7th International Conference on Cybernetics and Intelligent System (ICORIS), 235–240. https://doi.org/10.1109/ICORIS67789.2025.11296012 Santhoshkumar, S., Kalaimani, T. M., Chandra, H., Prasad, Parthasarathy, R., & Charaan, R. M. D. (2025). Machine Learning System for Comprehensive Student Assessment and Academic Performance Optimization. 2025 International Conference on Smart & Sustainable Technology (INCSST), 1–5. https://doi.org/10.1109/INCSST64791.2025.11210374 Song, J. Y. (2025). A Systematic Literature Review of Teacher Professional Development Based on Responsible AI Principles: Analysis of Domestic and International Research Trends (2020-2025). The Korea Association of Lifelong Education & Convergence (KALEC), 4(2), 37–55. https://doi.org/10.58207/kalec.2025.4.2.37 Stepanyan, K., Hasegawa, K., & Poon, H. (2025). What do I, as a student, think of my own work? Using summative self-assessment in a large technical module. Journal of Learning Development in Higher Education, (35). https://doi.org/10.47408/jldhe.vi35.1374 Studi, P., Matematika, P., Undikma, F., Zuhaida, N., Pujiastuti, E., & Zaenuri. (2025). Trends in Students Mathematical Problem-Solving Skills: A Systematic Review and Bibliometric Analysis of GeoGebra-Assisted Problem-Based Learning Research (2021-2025). Media Pendidikan Matematika, 13(2), 165–181. https://doi.org/10.33394/mpm.v13i2.18489 Suhaimi, S., Ghani, M. F. A., & Radzi, N. M. (2025). Does Student-centred Leadership Integrate with Collaborative, Distributive, and Instructional Leadership? A Recent Systematic Review (2021-2025). International Research-Based Education Journal, 7(2), 238–272. https://doi.org/10.17977/um043v7i22025p238-272 Syamsudin, F. I., Wiyono, K., Patriot, E. A., Ismet, I., Saparini, S., & Kamari, A. (2025). Trends in Technology Literacy Research (2021 to 2025): A Bibliometric Analysis with VOSviewer. Jurnal Materi Dan Pembelajaran Fisika, 15(2), 156–166. https://doi.org/10.20961/jmpf.v15i2.109121 Umri, N. A., Karnyoto, A., & Pardamean, B. (2025). The Impact of AI-Generated Hallucinations in Educational Settings: Trends, Gaps, and Future Directions. 2025 9th International Conference on Information Technology, Information Systems and Electrical Engineering (ICITISEE), 557–562. https://doi.org/10.1109/ICITISEE68184.2025.11355145 Utami, A., Rusmana, A. N., & Rahayu, D. (2025). CAPTURING CURRENT RESEARCH TRENDS ON THE UTILIZATION OF CHATGPT IN SCIENCE EDUCATION. Jurnal Pendidikan Matematika Dan IPA, 16(3), 564–581. https://doi.org/10.26418/jpmipa.v16i3.93046 Wali, M., Redhana, I. W., & Tika, I. N. (2025). TRENDS IN EDUCATIONAL GAMES TO IMPROVE STUDENTS' LEARNING MOTIVATION IN SCIENCE LEARNING: A SYSTEMATIC LITERATURE REVIEW. Jurnal Penelitian Pendidikan IPA, 11(11), 39–50. https://doi.org/10.29303/jppipa.v11i11.12121 Weng, Y., & Zhang, Y. (2025). Assessment of Personalized Learning in Immersive and Intelligent Virtual Classroom on Student Engagement. arXiv.org. https://doi.org/10.48550/arXiv.2501.07883 Xiao, F. (2025). Intelligent Deep Learning Framework for University Physical Education Teaching Quality Assessment. 2025 2nd International Conference on Software, Systems and Information Technology (SSITCON), 1–5. https://doi.org/10.1109/SSITCON66133.2025.11342279 Yunus, M., & Bachtiar, B. (2025). Beyond Access: Reframing Engagement, Assessment, and Feedback in Open and Distance Learning at Universitas Terbuka. International Journal of Learning, Teaching and Educational Research, 24(6), 492–511. https://doi.org/10.26803/ijlter.24.6.26 Zhang, N. (2025). Enhanced English Classroom Teaching Quality Assessment Using Hybrid Deep Learning Architecture. 2025 Third International Conference on Networks, Multimedia and Information Technology (NMITCON), 1–6. https://doi.org/10.1109/NMITCON65824.2025.11187842